Simultaneous Measurement of the DPOAE Signal Amplitude and Phase Changes - MICHALSKI, Wojciech; BOCHNIA, Marek; DZIEWISZEK, Wojciech (Archives of Acoustics, 2011)
Although the phenomenon of otoacoustic emission has been known for nearly30 years, it has not been fully explained yet. One kind of otoacoustic emissionis distortion product of the otoacoustic emission (DPOAE). New aspects of thisphenomenon are constantly discovered and attempts are made to interpret correctlythe obtained results. This paper discusses a new method of measuring DPOAEsignals based on double phase-sensitive detection, which makes possible a real-timemeasurement of the DPOAE signal amplitude and phase. The method was appliedfor measurements of DPOAE signals in guinea pigs. Sample records are presentedand the obtained results are discussed.